The GAL4 System: A Versatile Toolkit for Gene Expression in Drosophila. - Southall,TD; Elliott,DA; Brand,AH (CSH Protoc, 2008)
INTRODUCTIONThe generation of gain-of-function phenotypes by ectopic expression of known genes provides a powerful complement to the genetic approach, in which genes are studied or identified through mutations that generally reduce or eliminate gene function. The GAL4 system is a method for ectopic gene expression that allows the selective activation of any cloned gene in a wide variety of tissue- and cell-specific patterns. A key advantage of the system is the separation of the GAL4 protein from its target gene in distinct transgenic lines, which ensures that the target gene is silent until the introduction of GAL4. Recent modifications and adaptations of the GAL4 system to make the system inducible have further expanded its scope, enabling greater temporal control over the activity of GAL4. There are now large resources for the community, including thousands of GAL4 lines and a wide selection of reporter lines. Here we present an overview of the GAL4 system, highlighting recent developments and discussing methods for generating and analyzing transgenic flies for GAL4-mediated ectopic expression.